Confrontation and acculturation in college students (Revista de Psicología, 2019)
International migrations have reached the highest levels in history. Cultural distances among the countries of origin and the hosting countries affect acculturation processes, while different strategies to deal with them arise. These problematics involve different social organizations among which we find educational institutions. This research has as objective to inquire into confrontation styles, attitudes and anxieties before the different cultural groups based on an intentional sample of 66 students from public and private universities in the City of Buenos Aires. Adequate attitude levels towards multiculturalism, a medium level of positive emotions when connecting with foreign people and the prevalence of the focal-rational confrontation style were verified.
Keywords: Acculturation; Cross Cultural Differences; Anxiety; International Students; Cognitive Style.